2015
DOI: 10.3390/v7052683
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Convalescent Sera in Immune-Electron Microscopy to Detect Non-Suspected/New Viral Agents

Abstract: Negative staining electron microscopy methods can be employed for the diagnosis of viral particles in animal samples. In fact, negative staining electron microscopy methods are used to identify viruses, especially in minor species and wild animals, when no other methods are available and in cases of rare, emerging or re-emerging infections. In particular, immune-electron-microscopy with convalescent sera is employed to detect etiological agents when there are undiagnosed clinical outbreaks, when alternative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…5B). After PEDV infection in IPEC-J2 cells, viral particles assumed to be PEDV due to their mostly round shape (Lavazza et al, 2015) and diameter ranging from 95 to 190 nm (Lee, 2015) were found in the cytosol of the cells (Fig. 5B).…”
Section: Pedv Is a Potential Target Of Autophagymentioning
confidence: 99%
“…5B). After PEDV infection in IPEC-J2 cells, viral particles assumed to be PEDV due to their mostly round shape (Lavazza et al, 2015) and diameter ranging from 95 to 190 nm (Lee, 2015) were found in the cytosol of the cells (Fig. 5B).…”
Section: Pedv Is a Potential Target Of Autophagymentioning
confidence: 99%
“…Immunoelectron microscopy (IEM) is utilized when the number of viral particles in a sample is very low, when virions are pleomorphic and difficult to identify because they do not have a typical viral morphology or when the samples are "dirty" because the aggregated complexes are more easily observed [203]. It allows identification of the virus for specific antigen-antibody reaction and such identification is achieved by its morphology.…”
Section: Immunoelectron Microscopy Techniquementioning
confidence: 99%
“…Several variations of the method such as immune clumping or direct immunoelectron microscopy (DIEM) [206,207] or immune aggregation electron microscopy (IAEM) [203], solid phase immune electron microscopy (SPIEM) [199] and decoration [208] have been used. Hyperimmune sera, monoclonal antibodies or convalescent sera can be used in performing the technique [193,203].…”
Section: Immunoelectron Microscopy Techniquementioning
confidence: 99%
See 2 more Smart Citations